Making sense of the Sense Model: translation priming with Japanese-English bilinguals - Allen, David; Conklin, Kathy; van Heuven, Walter J.B. (John Benjamins Publishing Company, 2015)
Many studies have reported that first language (L1) translation primes speed responses to second language (L2) targets, whereas L2 translation primes generally do not speed up responses to L1 targets in lexical decision. According to the Sense Model (Finkbeiner, Forster, Nicol & Nakamura, 2004) this asymmetry is due to the proportion of senses activated by the prime. Because L2 primes activate only a subset of the L1 translations senses, priming is not observed. In this study we test the predictions of the Sense Model by using Japanese-English cognates, which allow us to manipulate the number of senses that words have in each language. Contrary to the predictions of the Sense Model, our results replicated the typical asymmetrical priming effects, suggesting that it is not the total activation of senses that drives the priming effect. Rather the results are more in line with theories that postulate slower, and thus ineffective, activation of semantics by L2 primes.